2017
DOI: 10.1038/s41593-017-0005-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of planarian TRPA1 by reactive oxygen species reveals a conserved mechanism for animal nociception

Abstract: All animals must detect noxious stimuli to initiate protective behavior, but the evolutionary origin of nociceptive systems is not well understood. Here, we show that noxious heat and irritant chemicals elicit robust escape behaviors in the planarian Schmidtea mediterranea, and that the conserved ion channel TRPA1 is required for these responses. TRPA1 mutant flies (Drosophila) are also defective in noxious heat responses. Unexpectedly, we find that either planarian or human TRPA1 can restore noxious heat avoi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 51 publications
(66 reference statements)
3
94
1
3
Order By: Relevance
“…These fragments were cloned into the pPR244-TRP vector using ligase independent cloning (45). The Smed-TRPA1-pGEMt plasmid was a gift from Dr. Marco Gallio (10).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These fragments were cloned into the pPR244-TRP vector using ligase independent cloning (45). The Smed-TRPA1-pGEMt plasmid was a gift from Dr. Marco Gallio (10).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been shown using RNA interference (RNAi) that the Transient Receptor Potential (TRP) channel, TRP ankyrin 1 (TRPA1), is required for avoidance behaviors in Schmidtea mediterranea in response to noxious heat and the pungent ingredient in mustard oil, allyl isothiocyanate (AITC) (10). The authors also showed that the noxious heat response was mediated by H 2 O 2 and/or reactive oxygen species which directly activate TRPA1, causing the planarian to avoid hot regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In animals, the only known and broadly conserved electrophile detecting sensors are the Transient Receptor Potential (TRP) nociceptive channel family (5)(6)(7), and the most studied among them is the Transient Receptor Potential Ankyrin-1 (TrpA1) (8)(9)(10). Reactive Brassicales plants typically produce ITCs upon tissue damage, which are highly toxic to non-adapted insects but not to mustard specialists, including S. flava (24).…”
Section: Introductionmentioning
confidence: 99%